2004
DOI: 10.1021/jp036846h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Stability of Double Six-Membered Rings of Oxygen-Bridged Silicon and Aluminum Atoms Related to Cation Site Occupancy in FAU Zeolites:  a DFT Study

Abstract: The electronic structure and relative stability of clusters with general composition (M n +) x / n H12Si12 - x Al x O18 with x = 0, 2, 4, M = H+, Li+, Na+, K+, Ca2+ forming double-six-membered rings (D6R), are studied by the B3LYP method. In Ca2H12Si8Al4O18 clusters, maximum separation of the Al atoms is favored, which implies a minimum number of Al−O−Si−O−Al linkages. A large number of isomers with Si,Al distributions strongly related to the type and location of the charge-compensating cations were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Therefore, we can conclude that clusters we used in the work are adequate to represent the interaction of H 2 and the acid sites in zeolite framework. From the relative stability of the Li + sitting sites in the Table 1, we found that site SI turned out to be the most stable location for Li + , which is in agreement with the study by D6Rs [24]. The SII site is preferred next and then follows the SIII site.…”
Section: + Sites In Fausupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, we can conclude that clusters we used in the work are adequate to represent the interaction of H 2 and the acid sites in zeolite framework. From the relative stability of the Li + sitting sites in the Table 1, we found that site SI turned out to be the most stable location for Li + , which is in agreement with the study by D6Rs [24]. The SII site is preferred next and then follows the SIII site.…”
Section: + Sites In Fausupporting
confidence: 89%
“…The selected bond distances and angles and the relative stability are reported in Table 1. Also shown in Table 1 for comparison are the results of experimental [29][30][31] and similar calculations with D6Rs [24] reported in the literature. It shows that the distance between the bridging oxygen and Li atom (R(Li-O)) of the present work has a better match to experiment than that in the D6Rs simulation.…”
Section: + Sites In Faumentioning
confidence: 90%
See 1 more Smart Citation
“…When the alkaline-earth Ca 2+ enters the SSZ-13 zeolite framework, it still appears in the form of a divalent cation Ca 2+ , which balances the negative charges brought by the two framework Al atoms. According to a study on faujasite (FAU) zeolite by Uzunova et al, 35 there are two possible locations of Ca 2+ in zeolite containing dual six-membered rings: one is located in the plane of a six-membered ring, and the other is located in the center of a hexagonal prism. The structural optimization in Figure 6 shows that the stable location of Ca 2+ in the SSZ-13 zeolite is the same.…”
Section: Computational Models and Methodsmentioning
confidence: 99%
“…[19] According to the plane‐wave results, the Cu(I) cations in the adsorption complexes remain coordinated to only two framework oxygen atoms even at the higher coordination sites, and they form relatively short bond lengths, which are more typical for Li cations than for transition metals. [41]…”
Section: Ordering Of Atoms At Tetrahedral Framework Sites and Extrafrmentioning
confidence: 99%